2016
DOI: 10.5005/jp-journals-10005-1325
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Pit and Fissure Sealant-containing Amorphous Calcium Phosphate to inhibit Enamel Demineralization

Abstract: Aim: To evaluate the effect of amorphous calcium phosphate (ACP)-containing pit and fissure sealant on inhibition of enamel demineralization in vitro.Materials and methods: Enamel specimens (n = 75) were prepared using freshly extracted noncarious human third molars. Box-shaped cavities (8 × 2 × 2 mm) on the buccal or lingual surfaces were prepared and restored with resin-based sealant (Concise™), ACP-containing sealant (Aegis®) or fluoride-containing sealant (Conseal-F™). The samples were acid challenged in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
2
19
0
3
Order By: Relevance
“…This was because the ACP on the zirconia ceramics regains the hydroxyl in the hydrothermal treatment, which was similar to the research of Ha 29) . On the other hand, it confirmed the ACP is a precursor to the formation of HAP, which is the final, stable product in the precipitation of the calcium and phosphate ions from neutral or basic solutions 30) . 32) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This was because the ACP on the zirconia ceramics regains the hydroxyl in the hydrothermal treatment, which was similar to the research of Ha 29) . On the other hand, it confirmed the ACP is a precursor to the formation of HAP, which is the final, stable product in the precipitation of the calcium and phosphate ions from neutral or basic solutions 30) . 32) .…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, ACP-containing bioactive materials stimulate mineral growth by increasing the calcium and phosphate concentrations within the lesion, especially in acidic environment, thereby shifting the thermodynamic driving forces of the solution toward the formation of apatite 30) . As the dissolution experiments results showed, Ca-P spots modified zirconia exhibited the higher Ca 2+ and PO4 3− release before hydrothermal treatment compared to after hydrothermal treatment (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Yassaei et al [74] reported the highest release of calcium ions and increased efficiency of Er:YAG laser to decrease demineralization when combined with CPP ACP products. A study by Hajizadeh et al [75] also found that the combined effect of Er:YAG laser with CPP-ACP and fluoride significantly increased dentin hardness and Er:YAG laser alone did not lead to increased dentin resistance to caries.…”
Section: Acp Incorporated In Pit and Fissure Sealantsmentioning
confidence: 95%
“…However, several factors may influence the long-term success of FS, such as oral biofilms containing S. mutans, which has esterase activity that hydrolyzes the ester bonds in materials containing methacrylate [3,4], or enamel demineralization in some parts of the teeth [5]. For this reason, particles such as fluoride or amorphous calcium phosphate (ACP) are added to FS materials to improve the preventive properties of sealants by increasing enamel remineralization and decreasing subsequent demineralization and secondary caries [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%